ADMINISTRATIVE GUIDELINE DEVELOPMENT OF EDUCATIONAL INSTITUTES BASED ON GOOD GOVERNANCE FOR SCHOOLS IN THE SECONDARY EDUCATIONAL SERVICE AREA ZONE 33 - puangsriken, Phongsiri; Chittranun, Thatchai (Journal of MCU Nakhondhat, 2020)
This research aimed to 1) current and desirable situation, 2) administrative guideline development of educational institutes based on good governance for schools in the Secondary educational service area zone 33 This research was divided into 2 periods. The first period was a study of research instrument comprised evaluation of the study of elements and indicators of educational institutes based on good governance for schools. Research sample included 350 teachers using Stratified Random Sampling. Research instrument comprised the second period evaluation of Administrative Guideline Development of Educational Institutes Based on Good Governance for Schools in the Secondary Educational Service Area Zone 33. Informants were 9 heads of each division. Research instrument was interview form. Statistical analysis comprised mean and standard deviation. This research found the following results: 1) Current conditions, school administration based on good governance principles for schools Under the Office of Secondary Educational Service Area 33, it is at the medium level. Desirable Conditions School administration based on good governance for schools. Under the Office of Secondary Educational Service Area 33, the overall is at the highest level. 2) Guidelines for school administration based on good governance principles for schools consisting of 4 aspects, 24 guidelines can be summarized as follows The administration should have a meeting to formulate an action plan in accordance with the operational agreements provided by the area. There is a clear action plan and recruitment and appointment procedures. There are activities for students to learn from real experience. Disclose procedures and guidelines for accepting students at every step. Jointly plan the educational administration between the school and those involved and decentralize Have a policy to instill good values and promote morality in all groups Give an opportunity for those involved to select textbooks Require stakeholders to listen to their opinions on activities that will affect the stakeholders.